Numerical Simulation of Radar Signal Reflected by Sea Surface with Different Sea Ice Concentration - Titchenko Yuriy; Karaev Vladimir Yur'evich; Panfilova Mariya Andreevna; Ponur Kirill Aleksandrovich; Kuznetsov Yaroslav; Meshkov Evgeniy Mihaylovich (Russian Journal of Earth Sciences, 2025)
Currently, methods of radar remote sensing at small incidence angles (from the vertical to 15∘) are actively developed. An important application of these methods is the determination of the presence and sea ice concentration. This paper presents an approach to numerical simulation of an experiment in which a reflecting surface with different sea ice concentrations is modeled and then the characteristics of the radar signal reflected by this surface for a given measurement geometry are modeled. Without loss of generality, in this paper we will consider a specific geometry of the DPR (Dual-frequency Precipitation Radar) radar on the GPM (Global Precipitation Measurement) mission satellite and only the Ku-band of this radar. The signal reflected by sea waves will be calculated within the Kirchhoff approximation. Since there is no generally accepted model for the signal scattered by the sea ice at small incidence angles, an empirical formula obtained from DPR data will be used as a model. The paper discusses a method for determining sea ice concentration using radar sensing data at low incidence angles.